Response of bispectral index to neuromuscular block in awake volunteers†. (14th July 2015) - Schuller, P. J.; Newell, S.; Strickland, P. A.; Barry, J. J.
Abstract : Background: The bispectral index (BIS) monitor is a quantitative electroencephalographic (EEG) device that is widely used to assess the hypnotic component of anaesthesia, especially when neuromuscular blocking drugs are used. It has been shown that the BIS is sensitive to changes in electromyogram (EMG) activity in anaesthetized patients. A single study using an earlier version of the BIS showed that decreased EMG activity caused the BIS to decrease even in awake subjects, to levels that suggested deep sedation and anaesthesia. Methods: We administered suxamethonium and rocuronium to 10 volunteers who were fully awake, to determine whether the BIS decreased in response to neuromuscular block alone. An isolated forearm technique was used for communication during the experiment. Two versions of the BIS monitor were used, both of which are in current use. Sugammadex was used to antagonise the neuromuscular block attributable to rocuronium. Results: The BIS decreased after the onset of neuromuscular block in both monitors, to values as low as 44 and 47, and did not return to pre-test levels until after the return of movement. The BIS showed a two-stage decrease, with an immediate reduction to values around 80, and then several minutes later, a sharp decrease to lower values. In some subjects, there were periods where the BIS was <60 for several minutes. The response was similar for both suxamethonium and rocuronium. Neither monitor was consistently superior in reporting the true state of awareness. Conclusions: These results suggest that the BIS monitor requires muscle activity, in addition to an awake EEG, in order to generate values indicating that the subject is awake. Consequently, BIS may be an unreliable indicator of awareness in patients who have received neuromuscular blocking drugs. Clinical trial registry number: ACTRN12613000587707.